EED and EZH2 constitutive variants: A study to expand the Cohen‐Gibson syndrome phenotype and contrast it with Weaver syndrome. Issue 4 (21st February 2019) - Griffiths, Sara; Loveday, Chey; Zachariou, Anna; Behan, Lucy‐Ann; Chandler, Kate; Cole, Trevor; D'Arrigo, Stefano; Dieckmann, Andrea; Foster, Alison; Gibney, James; Hunter, Matthew; Milani, Donatella; et al.
Abstract : Overgrowth‐intellectual disability (OGID) syndromes are characterized by increased growth (height and/or head circumference ≥+2  SD ) in association with an intellectual disability. Constitutive EED variants have previously been reported in five individuals with an OGID syndrome, eponymously designated Cohen‐Gibson syndrome and resembling Weaver syndrome. Here, we report three additional individuals with constitutive EED variants, identified through exome sequencing of an OGID patient series. We compare the EED phenotype with that of Weaver syndrome (56 individuals), caused by constitutive EZH2 variants. We conclude that while there is considerable overlap between the EED and EZH2 phenotypes with both characteristically associated with increased growth and an intellectual disability, individuals with EED variants more frequently have cardiac problems and cervical spine abnormalities, boys have cryptorchidism and the facial gestalts can usually be distinguished.